2009
DOI: 10.1016/j.ijgo.2009.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal bleeding following transvaginal oocyte retrieval

Abstract: Patients with severe intraperitoneal bleeding had a lower body mass index, a history of surgery, were younger, and had a moderate ovarian response; those with mild bleeding were young and had a high ovarian response.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 10 publications
0
20
0
1
Order By: Relevance
“…The most common complication is minor vaginal bleeding (1.4-18.4 %) secondary to accidental injury to the vaginal vessels [1]. The risk of pelvic infection (0.1-0.6 %) [2] and severe intraabdominal bleeding (0.05-0.2 %) [2][3][4][5] is very low. Though severe intra-abdominal bleeding usually occurs as a result of injury to sub-capsular ovarian vessels or small intra-follicular vessels [1], injury to pelvic vessels and coagulation abnormalities can also cause hemoperitoneum and retroperitoneal bleeding [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common complication is minor vaginal bleeding (1.4-18.4 %) secondary to accidental injury to the vaginal vessels [1]. The risk of pelvic infection (0.1-0.6 %) [2] and severe intraabdominal bleeding (0.05-0.2 %) [2][3][4][5] is very low. Though severe intra-abdominal bleeding usually occurs as a result of injury to sub-capsular ovarian vessels or small intra-follicular vessels [1], injury to pelvic vessels and coagulation abnormalities can also cause hemoperitoneum and retroperitoneal bleeding [6][7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Siristatidis et al [11] reported that four out of 542 women (0.74 %) who underwent TV-OPU were found to have abnormal platelets, and Fatum et al [12] reported of eight women in a cohort of 1,800 women (0.44 %) who had bleeding tendency disorder. While some units have a protocol of screening women routinely for coagulopathy [11] and some studies have emphasized the importance of undertaking coagulation profile before the procedure [5], a cross-sectional retrospective study [13] identified the need to screen 534 women for coagulation defects to prevent one case of excessive bleeding associated with abnormal coagulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Ancak Zhen ve ark.nın çalışmasında BMI 19-21 arasında olan zayıf kadınlarda kanama riskinin daha yüksek olduğu izlenmektedir. 17 Kanamayı engellemenin en kolay yolu müm-kün olduğunca az vajinal girişimde bulunmaktır. İşlem öncesi USG ile aspirasyonu planlanan foliküllerin gözlemlenmesi ve mümkünse renkli doppler ile muhtemel kan damarı komşuluklarının incelenmesi yardımcı olacaktır.…”
Section: Kanamaunclassified
“…In this context, it is unclear whether, or not, history of a prior OPU, similar to the history of a surgery, 9 pose any risk of increased blood loss in the course of OPU. We, herein, aimed to determine whether mean blood loss and hematologic parameters vary between women with and without the history of an oocyte retrieval procedure, in a non-anemic, unexplained infertility population who underwent OPU under general anesthesia, following controlled ovarian stimulation (COS).…”
Section: Introductionmentioning
confidence: 99%